SOLUTION
Write out the function given
![f(r)=\sqrt[]{r+6}-4](https://img.qammunity.org/2023/formulas/mathematics/college/iuyftxinuk309g2rh8yw2gkrkatibcopww.png)
The independent variable in the function above is r.
Hence
For f(-6), we have r=-6,
substitute into the function given
![\begin{gathered} f(-6),\text{ r=-6} \\ f(-6)=\sqrt[]{-6+6}-4 \\ f(-6)=\sqrt[]{0}-4=4 \\ Then,f(-6)=-4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/5zf8t03svcgqgdjfe5mb9jxyvcsk5a0l8m.png)
Hence, F(-6) = - 4
For f(43), we have
![\begin{gathered} f(43),\text{ r=43} \\ \text{Then} \\ f(43)=\sqrt[]{43+6}-4 \\ f(43)=\sqrt[]{49}-4=7-4=3 \\ \text{Hence, f(43) = 3} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/y7n3aeop3yf8x9z2fa7kp4y9owl7ctp5hu.png)
Thus, F(43) = 3
For f(x - 6), we have
![\begin{gathered} f(x-6)\Rightarrow r=x-6 \\ \text{Then } \\ f(x-6)=\sqrt[]{x-6+6}-4 \\ f(x-6)=\sqrt[]{x}-4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/jb9zjqhzuw89865jp87tw3s5ntzgn5r441.png)
Thus, f(x-6) = (√x) - 4